Rare Case of Multiple Intradural Extramedullary Spinal Schwannomas With Intramedullary Extension - Ahmed, Gasim (Cureus, 2021)
Spinal schwannomas are benign WHO grade I nerve sheath tumors that account for nearly 30% of all spinal neoplasm. Typically, these lesions are intradural extramedullary in location and are composed entirely of well-differentiated eosinophilic Schwann cells. Intramedullary schwannomas, however, are extremely rare due to the lack of Schwan cells in the normal spinal cord and represent 1% of all the spinal schwannoma population. The presence of such an intramedullary component makes diagnosis challenging as imaging features may resemble other intramedullary neoplastic entities. Here, we describe a case of a 56-year-old male patient who presented with an 18-month history of intermittent right-sided mid-thoracic pain secondary to multiple intradural extramedullary spinal schwannoma with intramedullary extensions. We also review the literature pertaining to the condition.